Associations between self-rated health and depressive symptoms among middle-aged and older adults in China: A cross-lagged panel analysis (2011–2020) - Shuyan Leng; Lihua Yao; Jiajia Deng (PLoS ONE, 2025)
Background As the aging of the population accelerates, mental health is important to the quality of life of middle-aged and older people, as well as to the healthcare system and the economy. This study focuses on the relationship between depressive symptoms and self-rated health in middle-aged and older people, as well as whether this relationship differs between urban and rural China. Methods Data from the China Health and Retirement Longitudinal Study (CHARLS). The final analysis included 10503 participants aged 45 years or above. The longitudinal cross-lagged panel analysis was used to assess the relationship between self-rated health and depressive symptoms. Results The model revealed a bidirectional relationship between self-rated health and depressive symptoms. Self-rated health at each time point had a significant effect on subsequent depressive symptoms, and vice versa. However, no urban-rural disparities in these relationships. Conclusion Self-rated health and depressive symptoms were interrelated over time among middle-aged and older adults. To ensure the mental health and quality of life in later life of middle-aged and older adults, it is essential to assess and manage both self-rated health and depressive symptoms.